PERAN GANDA WANITA KARIR DI KELURAHAN WENGKOL KECAMATAN TONDANO TIMUR KABUPATEN MINAHASA - Rambitan, Monica (HOLISTIK, Journal Of Social and Culture, 2014)
Speaking of women can not be separated from the concept of emancipation, because thevery thing that is the central theme during this long debate. Oppression of women is considered to deny the values hierarchy divine gift and a fraud against the dignity of women themselves. Because that then arises emancipation movements that leveling of rights between men and women.Women like this have to be more nimble as a result siagap and the dual role that mustbe lived, usually they use the services of a house keeper to help their tasks,and they should be able to devote time to interact with her husband and childrenÂ Keyword: Women, Economic, Social And Study